Attitude of second year junior college students towards physical activity : a case of one junior college - Mohd Azman Mohd Sidek. (2009)
Educators all over the world are constantly reviewing their curriculum and teaching methodology in order to ensure a balanced programme for students (Earl & Stennett, 1987). Programmes are challenged by the needs of our youths and as physical educators, we are constantly searching for ways to motivate our students "to develop lifelong physical activity habits" (p. 78, Tannehill & Zakrajsek, 1993). Therefore, students become a valuable source of information in helping teachers with their tasks.